Charting relationship marketing practice: it really didn't emerge in the 1970s. (16th November 2015) - Tadajewski, Mark
Abstract : Purpose: – This paper aims to provide a history of relational perspectives in marketing practice from the nineteenth through to the twentieth century. Design/methodology/approach: – This paper engages in a systematic reading of published histories of retailing practice using the key attributes of transaction and relationship marketing as a conceptual framework to interrogate whether earlier practitioners were committed to either approach. Findings: – This paper supplements the studies conducted in other domains that undermine the idea that relational practices were rejected in favor of transaction-type approaches during the industrialization of the USA and Canada. Practical implications: – The content of this paper provides textbook authors with a means to fundamentally revise the way they discuss relationship marketing. It has a similar pedagogic utility. Originality/value: – This paper studies the writings of practitioners known to be pioneers of retailing to unravel their business philosophies, comparing and contrasting these to known attributes of relationship marketing. It deals with an historical period that has not previously been studied in this level of detail by marketing historians.